THE PROFILE OF PRESCRIPTION OF ANTITUBERCULOSIS DRUG IN PATIENTS OUTPATIENT CARE AT ADVENTIST HOSPITAL MEDAN - Izar, Shaflina; Mayang Sari; Sri Handayani; Rizka Hasmi (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
Tuberculosis, a highly infectious ailment, is triggered by the bacterium Mycobacterium tuberculosis, primarily affecting the lung's functional tissue. Transmission occurs when a person inhales airborne saliva droplets containing the bacteria expelled by a tuberculosis patient through coughing, thus spreading the disease. This investigation sought to determine the attributes of tuberculosis patients receiving outpatient care, along with the pattern of anti-tuberculosis drug prescriptions at X Hospital Medan between July and December 2023. Metode; The study utilized a non-experimental approach because of its design and structure, which involved collecting survey data from the hospital's historical records. Ninety-six tuberculosis drug prescriptions issued during July–December 2023 were selected through random sampling. The study's findings revealed that, among 96 patients, the 46–55 age group comprised 22 individuals (22.9%), with females accounting for 55 patients (57.3%), and 94 patients (95.8%) utilized BPJS as their payment guarantor. The research indicated that Category I anti-tuberculosis drugs were prescribed more frequently than Category II anti-tuberculosis drugs for 92 patients (95.8%), and 59 patients (61.5%) at X Hospital received OAT-FDC, a commonly employed tuberculosis treatment. This study proposed that future research should outline the anti-tuberculosis medication prescription profile, using patients’ health information.